Effect of Adenine Sulphate on In Vitro Micropropagation of Acacia holosericea A. Cunn. ex G. Don Leaflets and Leaf Rachis Explants: Effect of Adenine Sulphate on In Vitro Micropropagation of Acacia holosericea - Shukla, Anupama; Anita Narang; Kaur, Surinder (Journal of Tropical Life Science, 2023)
In this study, different explant types (leaflets and leaf rachis) excised from 15-day-old seedlings of Acacia holosericea A. Cunn ex G. Don differentiated into multiple shoots when grown on B5 medium supplemented with various growth regulators. Results revealed that the shoots differentiated directly and indirectly in all the cytokinins [Benzyl adenine (BA); Kinetin (Kn), 2-isopentenyl adenine (2iP); Zeatin (ZN)] adjuvanted media. The ZN-supplemented B5 medium supported maximum multiple-shoot differentiation (3.2 ± 0.8 shoots per explant). However, with the adjuvant (AdS) present in the same ZN-supplemented B5 medium, the explants produced a higher number of shoots (7.0 ± 3.8 per explant). Likewise, the best leaflet regeneration medium was observed for B5 medium supplemented with 2.5 mg/L ZN and 200 mg/L of AdS. The B5 medium with the lower amount of ZN (1.5 mg/L) and 50 mg/L of AdS produced a maximum number of shoots (6.3 ± 3.8 shoots per explant) in the leaf rachis explants. Nearly 100% of the in vitro B5 basal medium-grown shoots developed roots directly at their base, consequently leading to their successful transfer to the soil.